RP-HPLC method development and validation of levamisole in pure and pharmaceutical formulation - B.Thangabalan; Anusha.G; S.Manohar Babu; B. Ram Sarath Kumar (International Journal of Pharmacy and Analytical Research, 2017)
A simple, fast, precise, selective and accurate RP-HPLC method was developed and validated for the determination of levamisole from pharmaceutical formulation. Chromatographic separation was achieved on a YMC C18 column (250 x 4.6mm, 5 µ particle size) using a mobile phase acetonitrile and water in the ratio of 80:20%V/V. The flow rate was 0.7ml / min and effluent was detected at 217nm. The retention time of levamisole was found to be 6.2min. Linearity was observed in the concentration range of 10 -50µg / ml .The method was validated according to ICH guidelines with respect to specificity, linearity, accuracy, precision and robustness. The method developed can be used for the routine analysis of levamisole.